A Review on Antibacterial Activity of Green Synthesis Zinc Oxide Nanoparticle - Azlan, Fauzul Adzim; Ainuddin @ Nordin, Ainun Rahmahwati (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This study assesses the antibacterial efficacy of synthesized zinc oxide nanoparticles produced using pomegranate leaves and flowers, Zingiber Officinale and Phyllanthus Niruri (Keezhanelli) leaves extract. In the study, zinc oxides were successfully employed to fabricate nanoparticles using leaves extract. The nanoparticles obtained were characterized spectroscopically. X-ray diffractive analysis (XRD) revealed the purity and crystallinity of the synthesized particles. The functional was confirmed using Fourier Transform Infra-Red (FTIR) Spectroscopy and the microstructure and composition of the nanoparticles are shown by scanning electron microscopy (SEM). By transmission electron microscope (TEM), the shape and size distribution of the synthesized particles is shown. Evaluation of the antibacterial efficacy of the fabricated nanoparticles showed that zinc oxide nanoparticle was effective against all selected pathogenic strains such as Staphylococcus aureus, Proteus Vulgaris and Escherichia coli used in the analysis. The effectiveness of these nanoparticles could be linked to their zone of inhibition as obtained using an optical microscope. This study revealed that the inhibition zone of the nanoparticles existed thus suggesting that zinc oxide nanoparticles can effectively be used as alternative antibacterial agents.